2022
DOI: 10.3390/nu14132611
|View full text |Cite
|
Sign up to set email alerts
|

Eating Disorders and Intimate Partner Violence: The Influence of Fear of Loneliness and Social Withdrawal

Abstract: Eating disorders are vulnerability factors that increase the likelihood of intimate partner violence. However, the mechanisms underlying this relationship are unclear. Although eating disorders have been associated with increased perception and fear of loneliness, they have also been associated with increased social withdrawal resulting from decreased enjoyment of social situations and poorer social functioning. The purpose of the present study was to examine the mediating role of fear of loneliness in the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…This falls in line with previous research that finds that Bulimia Nervosa (BN) can serve the function of establishing psychological and physical space following assault (Root & Fallon, 1989), and that Anorexia Nervosa can serve as a control mechanism over negative or dangerous interpersonal events (Peterson & Seligman, 1983). Indeed, as victims personally know their perpetrators in eight out of 10 cases of SA (Department of Justice, 2017), we may conceptualize the avoidance of activities as fear-driven (Momeñe et al, 2022) and intentional postassault.…”
Section: Functional Differences Between Sa and Non-sa Groupssupporting
confidence: 83%
“…This falls in line with previous research that finds that Bulimia Nervosa (BN) can serve the function of establishing psychological and physical space following assault (Root & Fallon, 1989), and that Anorexia Nervosa can serve as a control mechanism over negative or dangerous interpersonal events (Peterson & Seligman, 1983). Indeed, as victims personally know their perpetrators in eight out of 10 cases of SA (Department of Justice, 2017), we may conceptualize the avoidance of activities as fear-driven (Momeñe et al, 2022) and intentional postassault.…”
Section: Functional Differences Between Sa and Non-sa Groupssupporting
confidence: 83%
“…Results show that the most prevalent disorders are alcohol, EDs, CB, drugs and GD, respectively. The empirical literature has shown that EDs and CB are more prevalent in women, whereas GD and drugs are more prevalent in men (Granero et al, 2016;Chóliz et al, 2021;Momeñe et al, 2022a). Regarding alcohol, although the prevalence tends to be higher in men, both sexes show risky drinking patterns during youth (Delegation of the Spanish Government for the National Plan on Drugs, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…According to Kaur (2019), individuals who experienced more stressful childhood experiences and reported less ability to identify their moods (i.e., alexithymia) were more likely to use an addictive behaviour as a maladaptive coping mechanism. In addition, posttraumatic disorders are significantly more recurrent in young people in treatment for addiction and EDs than those without them, and are associated with a costlier treatment and worse prognosis (Wang et al, 2020;Momeñe et al, 2022a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations